Divorce, separation, and remarriage the transformation of family - Gianesini, Giovanna; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2016)
While the family remains a core social institution in every society, it is, nonetheless, an institution which continues to evolve. In many societies, divorce, separation, and remarriage have become a normative part of marriage and family life. These changes have, understandably, led to a great diversification of the behaviors, attitudes, and norms concerning marriage and family. In order to better comprehend these issues, this multidisciplinary volume of CPFR addresses topics including: marital instability, cohabitation and remarriage, step-parenting, divorce in later life, impact of divorce and separation on children, employment and the risk of divorce, marital dissolution and health, the role of extended kin in the process of divorce, the quality of relationships with former spouses, race/ethnicity and remarriage, economic factors and divorce/remarriage, and extra-marital affairs, among others.